2012
DOI: 10.1007/s12298-012-0133-7
|View full text |Cite
|
Sign up to set email alerts
|

Female plants of Hippophae salicifolia D. Don are more responsive to cold stress than male plants

Abstract: Hippophae salicifolia D. Don (Seabuckthorn) grows in stressful environment of high altitude under conditions of low temperature and low availability of water. We have studied gender based differences in physiochemical response to cold stress in male and female plants of Seabuckthorn. After 24 h of cold stress about 32 and 66 % higher electrolyte leakage (EL) was recorded in male and female plants respectively. Relative water content (RWC) at the end of 24 h stress was higher in male plants (~64 %) compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, numerous plants like Hippophae rhamnoides , Lepidium latifolium , etc. have a tendency to acclimatize in low temperatures; hence, they are successfully colonized in colder regions of the world, owing to the remarkable activities of their cold responsive-genes [5,6]. Proteins from these genes viz.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous plants like Hippophae rhamnoides , Lepidium latifolium , etc. have a tendency to acclimatize in low temperatures; hence, they are successfully colonized in colder regions of the world, owing to the remarkable activities of their cold responsive-genes [5,6]. Proteins from these genes viz.…”
Section: Introductionmentioning
confidence: 99%
“…Also GO and KEGG enrichment analysis showed that the DEGs were enriched in genes involved in antioxidant-related glutathione metabolism processes. Under cold stress, plant cells accumulate proline to protect against protein denaturation [ 52 ]; in cotton seedlings treated with EBR, the proline content was higher than in the control and the plants had greater cold tolerance. The cotton seedlings treated with EBR under cold stress had higher Pn.…”
Section: Discussionmentioning
confidence: 99%
“…The male and female plants are similar in morphology. Differences are only observed after 3-4 years of growth and only during blooming (Gupta et al, 2012).…”
Section: Introductionmentioning
confidence: 89%